1966
DOI: 10.1530/jrf.0.0110027
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Iufb on Reproduction in Mice

Abstract: Adult female mice with an intra-uterine foreign body in one horn were mated to normal males. Females were killed on Days 2 to 11, the reproductive tracts were removed, implantations were counted and the uteri and tubes were flushed to recover unimplanted ova. None of the thirty-two females killed after Day 5 had any evidence of implantations in the operated horn, and only 28% had implantations in the control horn. Forty-five per cent of these females had an average of3 \ m=. \ 9ova in the tubes of the operated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1967
1967
1990
1990

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…It is interest¬ ing to contrast this with the observations made on IUD-bearing mice. Greenwald (1965), Doyle & Margolis (1966), Marston & Kelly (1969) and Martin & Finn (1970) all agree that there is extensive infiltration of leucocytes into the stroma and the lumen of an IUD-bearing uterine horn. According to Martin & Finn, the effect seemed to be a local one, with many luminal leucocytes in the vicinity of the IUD, the numbers decreasing with distance.…”
Section: Discussionmentioning
confidence: 89%
“…It is interest¬ ing to contrast this with the observations made on IUD-bearing mice. Greenwald (1965), Doyle & Margolis (1966), Marston & Kelly (1969) and Martin & Finn (1970) all agree that there is extensive infiltration of leucocytes into the stroma and the lumen of an IUD-bearing uterine horn. According to Martin & Finn, the effect seemed to be a local one, with many luminal leucocytes in the vicinity of the IUD, the numbers decreasing with distance.…”
Section: Discussionmentioning
confidence: 89%
“…Unilateral uterine silk sutures induce unilateral sterility in rats, but most workers have found they induce bilateral sterility in mice. This appears to be due to the effective continuity of the uterine lumina between the two horns in most strains studied (Doyle & Margolis, 1966;Marston & Kelly, 1969a, b). We have consistently found unilateral silk threads to induce bilateral sterility , epithelial leucocytosis and epithelial abnormalities (Martin & Finn, 1978) in a minority of mice of our strain.…”
Section: Discussionmentioning
confidence: 96%
“…2). Doyle and Margolis (5) found that the entire mouse horn containing a foreign body was infertile, and that the fertility of the control horn was also markedly reduced. Thus the pattern of infertility in the mouse also corresponded to the pattern of polymorphonuclear leukocyte infiltration.…”
Section: Conventional Rats--as Seen Inmentioning
confidence: 99%